(untitled) (Proceedings of the YSU C: Geological and Geographical Sciences, 2006)
On the basis of mineralogo-paragenetic or gemological (gem-stone) phases within the bounds of Undersevan zone of ofiolite association of rocks are suggested factors of the forecast, criteria of search and attributes of genetic types of mineralization. In connection with ofiolites of Armenia it is obviously possible to draw gemologists, search-geologists and explorer-geologists attention to the real perspectives of estimation of scales displays of gem-stone raw materials and to put them forward for practical application.